Isolation and characterization of polymorphic microsatellite loci for Pistacia chinensis Bunge (Anacardiaceae) - Ding, Zhaohong; Lu, Jianbo (Silvae genetica, 2019)
Bunge (Anacardiaceae) is a native, dioecious, perennial arbor, and an important bioenergy plant. Twelve microsatellite markers were developed for to evaluate genetic diversity and population genetic structure when this species was subject to landscape fragmentation. Twelve polymorphic microsatellite loci were developed in using a microsatellite-enriched genomic library based on magnetic beads. These loci were characterized in 24 individuals from three populations located on Thousand Island Lake, Zhejiang Province, China. The number of alleles per locus varied from three to sixteen. The observed and expected heterozygosity ranged from 0.1250 to 0.8750 and 0.2333 to 0.8917, respectively. These microsatellite loci will be applied in further studies on the population genetic diversity and genetic structure of . This study will improve understanding of the effects of landscape fragmentation, and help conserve and manage the species.